The archaeology of the Johor-Riau-Lingga Malay Kingdom from the 16th to 19th century C.E.: a re-evaluation - Asyaari Muhamad, (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2020)
This topic focuses on the later history and archaeological heritage of the Malay Johor-Riau-Lingga Sultanate dated from the 16th to 19th century ce (Current Era). This paper includes the study of Kota Sayong Pinang, Batu Sawar, Kota Seluyut, Kampung Makam, Kota Panchor and Kota Johor Lama. The supporting evidence for the discussion in this paper includes a textual study of several Malay texts (such as Sejarah Melayu, Sejarah Negeri Johor, and Sejarah Petempatan di Sepanjang Sungai Johor) and the archaeological record. This research shows that the remains of old forts such as found at Kota Johor Lama, Kota Sayong Pinang, Kota Batu Sawar and Kota Seluyut represent a lot of the material historical and archaeological evidence. The burial sites of the royalty and ruling class, the discovery of gold dinar coins, various weaponry and an overwhelming abundance of ceramics (mostly broken) are among the important discoveries throughout the research. As much as 211 tombstones of the Aceh style were discovered in the state of Johor. The oldest Acheh tombstone in Johor was dated 1453 ce (or 857 Hijrah according to the Islamic calendar) and ceramics dated between 11th and 14th century strongly suggests that there was an earlier kingdom prior to the Malay JohorRiau-Lingga Sultanate. Among the earlier ceramics found include Chinese Song, Sawankhalok, Khmer, Vietnamese and Sukhothai dated from the 13th to 15th century. Even so, most of the archaeological evidence along the Johor River were destroyed due to deterioration, development of the surrounding and various conflicts among the ruling kingdoms.